Prospects for the use of flavonoid substances in pulmonary fibrosis (review of experimental studies) - E. A. Gubareva; A. L. Semenov (Южно-Российский онкологический журнал, 2024)
Pulmonary fibrosis develops both spontaneously and as a result of lung damage by radiotherapy and chemotherapy, infectious diseases, and inhalation of harmful substances and particulate matter. In this case, normal tissue repair is disturbed: instead of regeneration of normal lung cells, the damaged tissue is replaced by fibrotic one consisting of dense collagen fibers. This leads to loss of lung tissue elasticity and impairment of its function, which significantly reduces the quality of patients’ lives. The search for drugs for interstitial fibrotic lung diseases remains an urgent task, since the existing antifibrotic drugs only slow down disease progression and have side effects that significantly reduce the patients’ quality of life. It is believed that natural polyphenolic substances, in particular flavonoids, can be used for the treatment of pulmonary fibrosis. Flavonoids present in various fruits, vegetables, tea and wine show a wide range of biological activities. They have antioxidant, anti-inflammatory and immunomodulatory properties, making them promising for the treatment of various diseases, including pulmonary fibrosis. Some studies have shown that flavonoids can inhibit myofibroblast activation and collagen production, which is directly related to the fibrotic process. Flavonoids are safe and can influence the hallmarks of fibrosis: oxidative stress, inflammation, cell proliferation and differentiation. To date, a large amount of experimental data confirming the antifibrotic effect of flavonoids has been accumulated. In recent years, clinical studies have been conducted to investigate the efficacy and safety of flavonoids in patients with pulmonary fibrosis. For example, quercetin and curcumin are being explored and have shown encouraging results in reducing markers of inflammation and fibrosis in the lung. However, the main obstacle to the widespread introduction of flavonoid substances into clinical practice remains their low oral bioavailability and rapid metabolism. The experimental data on the effect of flavonoids on the development of pulmonary fibrosis is analyzed in this review. The perspectives for improving their bioavailability using modern delivery systems (nanoparticles, liposomes, etc.), as well as dosage forms for topical application, are discussed in this paperwork.